POTRET AWAL SELF-EFFICACY SISWA SMP PADA MATERI ZAT ADITIF - Herlina, E.; Suprapto, P.K.; Badriah, L.; Hernawati , D. (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study aims to analyze the self-efficacy of students of SMP N 8 Banjar class VIII on the material of additives. Self-efficacy is important as one of the psychological aspects that play a role in learning. Specifically, the role of self-efficacy in learning includes increasing students' self-confidence in understanding difficult material, encouraging motivation to learn with greater effort and persist in facing challenges, helping students set realistic goals according to their abilities, and encouraging the selection of effective learning strategies. The method used is descriptive quantitative with a questionnaire consisting of 27 questions and involving 32 students. Self-efficacy is measured based on 3 dimensions based on magnitude level, generality, strength. The results of the study showed an average value of each dimension, namely: magnitude level (66), generality (70) and strength (63). The overall average value of the self-efficacy dimension is 66 with a sufficient category. The less than optimal study was caused by students' lack of confidence in their abilities, giving up easily if given more complex tasks and low learning motivation. Strategies such as providing positive feedback, real-world problem-based learning, more contextual learning models, and social support that encourage students' self-confidence and resilience in facing academic tasks are recommended. ABSTRAKPenelitian ini bertujuan untuk menganalisis self-efficacy siswa SMP N 8 Banjar kelas VIII pada materi zat aditif. Self-efficacy ini penting sebagai salah satu aspek psikologis yang berperan dalam pembelajaran. Secara spesifik, peran self-efficacy dalam pembelajaran meliputi peningkatan kepercayaan diri siswa dalam memahami materi yang sulit, mendorong motivasi untuk belajar dengan usaha lebih keras dan bertahan menghadapi tantangan, membantu siswa menetapkan tujuan yang realistis sesuai dengan kemampuan mereka, serta mendorong pemilihan strategi belajar yang efektif. Metode yang digunakan adalah deskriptif kuantitatif dengan angket kuesioner sebanyak 27 butir soal dan melibatkan 32 siswa. Self-efficacy  yang diukur berdasarkan 3 dimensi berdasarkan magnitude level, generality, strength. Hasil penelitian menunjukkan nilai rata-rata tiap dimensi yaitu : magnitude level (66), generality (70) dan strength (63). Nilai rata-rata secara keseluruhan dimensi self-efficacy yaitu 66 dengan kategori cukup. Kurang optimalnya penelitian ini disebabkan oleh kurang yakinnya siswa terhadap kemampuan yang dimiliki, mudah menyerah jika diberi tugas yang lebih komplek serta motivasi belajar yang masih rendah. Disarankan strategi seperti pemberian umpan balik positif, pembelajaran berbasis masalah nyata, model pembelajaran yang lebih kontekstual, serta dukungan sosial yang mendorong rasa percaya diri dan ketahanan siswa dalam menghadapi tugas akademik.